PENGARUH PEMANFAATAN TEKNOLOGI INFORMASI OLEH PENYULUH PERTANIAN LAPANGAN TERHADAP FUNGSI BPP SEBAGAI PUSAT PEMBELAJARAN DI KABUPATEN LAMPUNG TENGAH - Irawan, Sahrul Ari; Gultom, Dame Trully; Listiana, Indah; Yanfika, Helvi (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
The research aims to find out the level of utilization of information technology by Field Agricultural Extension and analyze the influence of information technology utilization by Field Agricultural Extension on the Function of BPP as a Learning Center. The research was conducted in December 2021 - January 2022 in Central Lampung Distriet on four BPP namely BPP Gunung Sugih, Seputih Raman, Kota Gajah, and Trimurjo. Respondents in this study were Field Agricultural Extension as many as 40 people.  Research methods were conducted in a descriptive quantitative and simple linear regression analysis. The results of this study showed field agricultural extensionists have utilized information technology by 57,50 percent.  Utilization of information technology was utilized as part of information and data centers, governance management, communication, and data analysis. There was no influence between the utilization of information technology by Field Agricultural Extension to the function of BPP as a learning center.  The Agricultural Extension Center was optimized for various activity centers such as agribusiness consultation, agricultural development center, data and information center and so on.